Intracranial Hypertension Due to Meningioma of the Unique Transverse Sinus - Mariniello, G. (Neuroradiol J, 2013)
We describe a 28-year-old woman with intracranial hypertension due to a meningioma invading the unique transverse sinus (with absent contralateral sinus). Clinical remission and normalization of orbital echography were obtained by resection of the intradural tumor and peeling of the dural attachment. In such cases, resection and reconstruction of the involved sinus segment is at high risk of venous infarction. Endovascular stenting of the obstructed sinus is a valid alternative when the stenosis is not remarkable. Single tumor removal may lead to partial sinus decompression and increased venous flow, resulting in long-term clinical remission.